A low power and high speed 45 nm CMOS dynamic comparator with low offset - Brindha, Kulothungan; Manjula, Jothilingam (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
The development of efficient data converters necessitates the design of low-power and high-speed comparators with low offset. Data converters, such as analog to digital converters (ADCs) and digital to analog converters (DACs), are critical components in applications like wireless communication, multimedia, and sensor interfaces. To enhance the performance of these data converters, improving the speed and power efficiency of comparators becomes crucial. Designing dynamic comparators with low power consumption and high-speed capabilities greatly enhances the sampling rate and accuracy of data converters. Moreover, addressing the offset voltage of comparators becomes crucial for achieving accurate signal conversion. To fulfill this need, a novel dynamic comparator has been designed, featuring high-speed operation, low-power consumption, and minimal offset. The circuit comprises a pre-amplifier with a charge pump, followed by a decision circuit and an output stage. Through simulations, the comparator has demonstrated low power consumption of 15.04 µW, a delay of 80.51 ps, and an extremely low offset voltage of 8 µV. These characteristics make it highly suitable for data converters. The comparator operates at a clock frequency of 1 GHz and a supply voltage of 1 V, and the simulation was conducted using the Cadence Virtuoso tool in a 45 nm CMOS technology.